Edukasi dan praktik pijat oksitosin pada ibu menyusui di desa Purba Nauli Kecamatan Angkola Muara Tais Kabupaten Tapanuli Selatan - Harahap, Syera Mahyuni (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
In the breastfeeding process, there are often obstacles in the production and production of breast milk, so it is necessary to make efforts to express breast milk for some postpartum mothers. In this effort there are 2 things that affect the production and expenditure. Breast milk production is influenced by the hormone prolactin while expenditure is influenced by the hormone oxytocin Through oxytocin massage, namely massage or stimulation of the spine, the neurotransmitter will stimulate the medulla oblongata directly sending messages to the hypothalamus in the posterior pituitary to release oxytocin, causing the breasts to secrete milk. This community service aims to increase mothers' knowledge about oxytocin massage and so that mothers feel the benefits of oxytocin massage. The materials used in this community service are brochures or leaflets containing techniques for performing oxytocin massage. The method of implementing this community service is by giving lectures to provide theory about oxytocin massage and practicing oxytocin massage management. With this service, mothers better understand the benefits of oxytocin massage and feel the benefits of the massage The result of this community service activity is that mothers understand and feel the benefits of oxytocin massage that has been carried out and delivered. Evaluation in this community service activity is carried out by conducting direct demonstrations of the participants.